Relationship of Strategic Management Practices and Performance of Percetakan Nasional (M) Berhad - Mohd Imran, Mohd Husin (2011)
This paper discusses mainly about strategic management and its implications especially in the organization. The paper aims to develop an understanding of the role of strategic management in the proper allocation of business resources on businesses today especially in the global business environment. This study's objective is to present the importance of having the right organization that fits to the strategy of a company. It aims to determine the effect of the organization to the implementation of a strategy especially a global strategy that can bring changes to the production process, distribution and marketing channel that will demand new ways of organization. This study was done among 200 exempt staffs in Percetakan Nasional Malaysia Berhad. Data were gathered through questionnaires and was being analyzed by using Statistical Package for Social Science (SPSS) version 19.